Presencia en Costa Rica de Echinacoccus oligarthrus Diesing 1863, colectado en el intestino delgado de Felis concolor costaricensis - Brenes Madrigal, Rodrigo R.; Muñoz Montoya, Guillermo; Monge Ocampo, Eduardo; Rojas Herrera, Gerardo (Revista de Biología Tropical, 1973)
Echinococcus oligarthrus Diesing, 1863, from the small intestine of a puma, Felis concolor costaricensis, is reported for the first time in Costa Rica. It had been previonsly reported from Brazil, Colombia and Panamá.